Fosfomycin-Containing Regimens for the Treatment of Central Nervous System Infections in a Neonatal Intensive Care Unit: A Case Series Study - Angelica Lenzi; Barbara Saccani; Marco Di Gregorio; Francesco Rossini; Alessio Sollima; Alice Mulè; Federica Morucci; Silvia Amadasi; Benedetta Fumarola; Paola Antonia Lanza; Silvia Lorenzotti; Evelyn Van Hauwermeiren; et al. (MDPI AG, 2024)
Central nervous system infections are among the most severe infectious conditions in the neonatal period and are still burdened by significant mortality, especially in preterm infants and those with a low birth weight or other comorbidities. In this study, we examined the role of fosfomycin-containing antibiotic regimens in neonates with central nervous system infections. We included six neonates over a period of five years: four with meningitis and two with cerebral abscesses. All patients underwent fosfomycin therapy after failing first-line antibiotic regimens. Of the six neonates, two died; two developed neurological and psychomotor deficits and two recovered uneventfully. None of the neonates experienced adverse reactions to fosfomycin, confirming the safety of the molecule in this population. In conclusion, the deep penetration in the central nervous system, the unique mechanism of action, the synergy with other antibiotic therapies, and the excellent safety profile all make fosfomycin an attractive drug for the treatment of neonatal central nervous system infections.